2008
DOI: 10.1111/j.1468-3083.2007.02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Actinic keratosis: an occupational and environmental disorder

Abstract: Solar ultraviolet light electromagnetic waves are a known environmental carcinogenic agent closely associated with the development of skin cancer in light-complexioned individuals. Outdoor workers have higher annual exposure to ultraviolet light. We will review the topic of actinic keratoses among these individuals as this common rudimentary form of superficial cutaneous squamous cell carcinoma is explored in greater detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Therefore, in addition to providing resistance to environmental stress cracking and aging, they also improve the physical and optical properties of the organic polymer. 6,7,10 The energy difference between the valence band and the conduction band is known as the band gap. Nanosized zinc oxides have a band gap of around 3.37 eV, corresponding to a wavelength of 376 nm, which helps them to absorb effectively the light that matches or exceeds this band gap energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to providing resistance to environmental stress cracking and aging, they also improve the physical and optical properties of the organic polymer. 6,7,10 The energy difference between the valence band and the conduction band is known as the band gap. Nanosized zinc oxides have a band gap of around 3.37 eV, corresponding to a wavelength of 376 nm, which helps them to absorb effectively the light that matches or exceeds this band gap energy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these physical principles, UV shielding is the result of nanoparticle absorption and scattering. [9][10][11] The band gap value is 3.0 eV for the rutile type and 3.2 eV for the anatase type of Ti oxides. The wavelength of the light required for photoexcitation is 1240 (Planck's constant, h) / 3.2 eV (band gap energy) ¼ 388 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Facial AK is a differential diagnosis of cutaneous melanoma (lentigo maligna) since pigmented facial AK may have a broken-up pseudonetwork. [28][29][30][31][32] Pseudonetwork can be observed in dermatoscopic examination of certain benign pigmented facial lesions such as AK, ephelide, and junctional nevus. Zaluadek et al observed four essential dermatoscopic features in facial AK and defined the combination of these features as "strawberry" pattern [ Table 3 and Figure 6].…”
Section: Introductionmentioning
confidence: 98%
“…Peaks are seen at 405, 505, 540, 580 and 635 nm. Often a light source (LED) with a narrow band at 634 nm is employed [2, 14]. By means of activation oxygen radicals are produced and the altered cells are destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…AK are viewed as an carcinoma in situ variant of squamous cell carcinoma [1]. Today various therapy forms are available to treat actinic keratoses, among others, physical ablation via curettage, cryotherapy, chemotherapeutic topical therapies, immunomodulators and photodynamic therapy (PDT) [2, 3]. We report on a proof of concept study on topical therapy of actinic keratoses with low‐dose 5‐fluorouracil and sali‐cylic acid.…”
Section: Introductionmentioning
confidence: 99%